Contract law - Elliott, Catherine (Pearson/Longman, 2009)
It is essential for students on law and commercial degree programmes to have a clear understanding of contract law, yet the subject can difficult to grasp for the newcomer. This book clarifies the essential concepts behind the law, making it easier for students to understand and apply the legal rules. Each chapter includes discussion of problems with the current law, helping the student to develop a critical and analytical approach. The book also considers the forces affecting contract law today, such as the increase of e-commerce and the growing impact of Europe, and how the law may need to reform to meet modern needs.